Mediator of DNA damage checkpoint 1 (MDC1) regulates mitotic progression. - Townsend, K; Mason, H; Blackford, A; Miller, E; Chapman, R; Sedgwick, G; Barone, G; Turnell, A; Stewart, G (2009)
Human mediator of DNA damage checkpoint 1 (hMDC1) is an essential component of the cellular response to DNA double strand breaks. Recently, hMDC1 has been shown to associate with a subunit of the anaphase-promoting complex/cyclosome (APC/C) (Coster, G., Hayouka, Z., Argaman, L., Strauss, C., Friedler, A., Brandeis, M., and Goldberg, M. (2007) J. Biol. Chem. 282, 32053-32064), a key regulator of mitosis, suggesting a possible role for hMDC1 in controlling normal cell cycle progression. Here, we extend this work to show that hMDC1 regulates normal metaphase-to-anaphase transition through its ability to bind directly to the APC/C and modulate its E3 ubiquitin ligase activity. In support of a role for hMDC1 in controlling mitotic progression, depletion of hMDC1 by small interfering RNA results in a metaphase arrest that appears to be independent of both BubR1-dependent signaling pathways and ATM/ATR activation. Mitotic cells lacking hMDC1 exhibit markedly reduced levels of APC/C activity characterized by reduced levels of Cdc20, and a failure of Cdc20 to bind the APC/C and CREB-binding protein. We suggest therefore that hMDC1 functionally regulates the normal metaphase-to-anaphase transition by modulating the Cdc20-dependent activation of the APC/C.